Landscape of Peace Mechanisms of Social Control on Lamotrek Atoll, Micronesia - Werle, Kerstin J. S.; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2014)
Kerstin Werle$1 (Bs work is based upon a year of fieldwork on Lamotrek and Yap, belonging to a group of islands with a matrilineal culture. Although a trend to the lifestyle of the Western world can be found everywhere on the islands, traditional customs, a gendered division of labour, and subsistence techniques prevail. Kerstin Werle carried out her research according to classical anthropological methods, supplementing the available specialist literature on the widespread Micronesian atolls with a valuable overview. Her book shows how the ideal of an old and wise woman, contained in the cultural symbol lavalava, is faced with a young society. Due to the extremely limited space on the small atolls, individual plots of land have become historically, culturally, and emotionally significant places, all of which have been ascribed their own individual character. With the help of these personalized places, people on Lamotrek pursue local politics. Contents Womens$1 (BPower, Gender Roles and Pictures of Ageing The Anthropology of Landscape in Fieldwork Settings Emotions as Expression of Cultural Norms Culture as a Process of Collective Localisation Target Groups Lecturers and students in Sociology, Psychology, Micronesian Studies, Cultural Anthropology Journalists, media experts, social politicians, development workers, teachers The Author Kerstin Werle has studied sociology and cultural anthropology with a focus on India and Micronesia. Currently, she is living in Breisach and working as a freelance writer.s
Women's Power, Gender Roles and Pictures of Ageing -- The Anthropology of Landscape in Fieldwork Settings -- Emotions as Expressions of Cultural Norms -- Culture as a Process of Collective Localisation.
Keywords: Social sciences; Sociology; Social groups; Family; Youth; Sex (Psychology).; Gender expression; Gender identity; Social Sciences; Social Sciences, general; Gender Studies; Sociology of Familiy, Youth and Aging; Electronic books